Mapping the Evolution of Tourism Studies in Bali: A Comprehensive Network Analysis - Ramang H. Demolingo; Putu Pramania Adnyana; Titus Indrajaya; M.A. Inez Saptenno (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This study aims to comprehensively review Bali tourism-related literature from 1979 to 2022. The research employed a mixed-methods approach, combining bibliometric techniques and a literature review. The analysis includes 128 international publication records from the Scopus database that contain the keywords "tourism in Bali." The study categorizes research trends in Bali tourism into four primary categories: research sites, research methods, research scopes, and tourism-related components. However, the study is limited by its reliance on a single database, Scopus. These findings can serve as hypotheses for future investigations. This study is anticipated to provide a valuable resource for scholars and researchers interested in studying Bali tourism, representing the first and most current review of the literature on the evolution of tourism studies in Bali over the past four decades.